Mathematical modeling of the conventional drying of wood - Sandoval-Torres, Sadoth (Instituto de Ecología, A.C., 2016)
The kiln-drying of lumber is a very important stage into wood-based products processing. During drying process, some defects are produced due to the variable moisture and heat distribution inside of material. In order to optimize the kiln-drying of lumber is important to take into account the transport phenomena controlling the heat and mass transfer in the solid. Due to its physical properties, the hardwoods are a very important raw material, since its hardness, colour, dimensional stability and high resistance to weathering give them a very important commercial value. At the last years, the drying process modelling has been an effective tool to optimize such operations; these models associates energy, mass and momentum balances, which can be expressed as differential equations that are numerically solved to obtain particularly solution for each problem. In this work, the heat and mass transfer mechanisms presents in kiln-drying of lumber are explained, heat and mass transport equations are written, and finally moisture and temperature profiles for European Oakwood Quercus pedoncula during kiln-drying are presented.